Analysis of additives for bio-based engine oil for a two stroke marine engine / Keong Le-Onn - Keong, Le-Onn (2021)
Bio-based oil synthesis through Neopentyl glycol (NPG) and Trimethylolpropane (TMP) ester are used to produce biodegradable bio-lubricant for a two stroke marine engine. Two stroke engine, specifically for marine activities, widely uses synthetic lubricant in the fuel-oil mixture as it is easily available and at low cost. This has huge impact to the environment as two-stroke marine engine release its byproduct directly into the aquatic environment during its operation and the less stringent law encourage this to occur widely around the world. Bio-based oil with the combination of Group II synthetic oil with various composition allow us to find the optimum composition to produce the similar or better performance of fuel-oil mixture compared to using synthetic oil entirely. Additives of Graphene Oxide (GO), Anti-Oxidant (AO), PIB and solvent are added into this bio-based oil mixture to enhance its performance and capability of using bio-based oil. The physicochemical properties of viscosity, density and VI ratio are obtained through advance viscometer. Sample with 50% bio-based oil and 50% Group II mineral oil has the most optimum result among the tested composition, including the baseline reference lubricant suggested by the two-stroke marine engine manufacturer. An improvement of 28.36% when compared to the baseline sample in terms of Viscosity Index (VI) is observed, whereby Sample 3 has VI value of 160.4. The higher VI allow it to operate at various temperature range which is a key factor marine use as the environment varied throughout the day. Through the wear scar diameter test and obtaining the coefficient of friction, the bio-based oil alone has outrun the synthetic oil, both from Group I and Group II base oil. This factor is critical to ensure engine lubrication of bio-based oil is on par or perform even better for engine performance. Each sample of bio-based oil mixture is tested in actual two-stroke marine engine to find out the deposition of carbon on the spark plug. Sample with bio-based oil from PNAF-NPG ester shows the most optimum result with the least amount of carbon iv deposition on the spark plug and at dry condition for moisture rating. Whereas for TMP ester, composition of this bio-based oil that is more than 30% will cause carbon to deposition on the spark plug – however the moisture rating remained low. Complex microstructure of TMP required higher temperature during combustion process to completely process all the TMP. Hence, TM would be useful to be used on engine with higher revolutions. The similar result is observed when using a lower revolution two-stroke engine. As such, the usage of bio-based oil from PNAF-NPG is acceptable and able to provide satisfactory results on low or high revolution two-stroke engine.